Pemberdayaan Ekonomi Petani Hortikultura Melalui Peningkatan Produktivitas, Integrasi Pasar dan Penguatan Kelembagaan Kelompok Tani Tunas Baru di Kelurahan Malawele, Distrik Aimas, Kabupaten Sorong - Nugroho, Adi; Karto, Andriani; F. Binter, Arnold; Pasaribu, Sandi H.; Frasawi, Orpa; Seme, Alfin; Yamese, Delfianti; Kalaibin, Yulius; Djitmau, Fanda (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This Community Service program was conducted in Malawele Village, Aimas District, Sorong Regency, to empower farmers’ economic capacity through improvements in farming productivity, market integration, and strengthening of farmer group institutions. The target group of the activity was the Tunas Baru Farmer Group, whose members cultivate horticultural crops, particularly mustard greens and long beans. The program was implemented using a participatory and applicative approach, placing farmers as active subjects in all stages of the activity, including problem identification, counseling, technical training, marketing assistance, and institutional strengthening. The results of the program indicate an improvement in farmers’ knowledge and skills related to cultivation techniques, increased awareness of the importance of market access and collective marketing, and enhanced cooperation and participation within the farmer group. Furthermore, the strengthening of the Tunas Baru Farmer Group contributed to its role as a forum for joint decision-making and collective farm business planning. Overall, the Community Service activity demonstrated positive initial impacts on farmer economic empowerment and provided a foundation for sustainable horticulture-based local economic development in Malawele Village.